Evaluation of the mechanical properties of recycled glass fibers-derived three dimensional geomaterial for ground improvement - Mujah, Donovan; Ahmad, Fauziah; Hazarika, Hemanta; Safari, Aboulfazl (Elsevier Science, 2013)
This research was aimed to study the potential use of recycled glass fibers-derived three dimensionalgeomaterial (8FG MAT) obtained from industrial glass fiber wastes to innovate a sustainable, costeffective geosynthetic for ground improvement in problematic soil applications. The ready availability, high tensile strength, lightweight and non-biodegradable characteristics of glass fibers further elevate their advantages as compared to the presently adopted geosynthetics in soft soil reinforcement condition. In this study, mechanical properties of recycled glass fibers and their ‘8’ shape form samples as well as the pullout resistance force of 8FG MAT were investigated by considering glass fibers’ layer thickness, shape formation and orientation in a laboratory scale model. It was observed that the tensile and yield strengths of overall geomaterial samples significantly increase as strip layers thickness increase. Results from both the tensile strength and pullout resistance force indicated similar trend of increasing in strength values with test conducted using other type of geosynthetics in various soil media to simulate the action of different soil conditions at real sites.